Sepsis-Induced Myocardial Dysfunction in Pediatric Septic Shock: Prevalence, Predictors, and Outcome—A Prospective Observational Study - Swami, Viresh S.; V., Lalitha A.; Ghosh, Santu; Reddy, Mounika (Journal of Pediatric Intensive Care, 2021)
There is a paucity of literature on the prevalence, predictors, prognostic markers, and outcomes of sepsis-induced myocardial dysfunction (SMD) in pediatric septic shock. The objectives of our study were to estimate the prevalence of SMD in pediatric septic shock by point-of-care functional echocardiography (POCFE) and to study the association of SMD with severity of illness, organ dysfunctions, and outcomes. This prospective, observational study was conducted over a period of 1 year (from July 2018 to July 2019) in a 12-bed, tertiary pediatric intensive care unit (PICU) of an academic and referral hospital in South India. Children presenting with septic shock were enrolled in the study. POCFE was done within 6 hours of PICU admission and patients were categorized as having SMD based on POCFE findings. The prevalence of SMD (left ventricle ± right ventricle) was 32% (32/100). More than half of the children (54.5%) died in SMD group, whereas only 7.5% died in non-SMD group (p < 0.001). SMD was associated with higher organ dysfunctions, worse patient outcomes, and was found to be an independent predictor of mortality. The median lactate levels were higher in SMD group (3.15 [2.7, 5] vs. 2 [1.3, 2.7], p < 0.001) as compared with non-SMD group. We observed significantly lower median lactate clearance at 6 hours in SMD than non-SMD (30.0% [−14.44, 44.22] vs. 59.8% [45.83, 71.43], p < 0.001). Lactate levels at 6 hours with a threshold of 2.4 mmol/L was a good predictor of SMD with sensitivity and specificity of 73 and 80%, respectively. SMD is not an uncommon entity in children with septic shock. SMD was associated with worse patient outcomes, organ dysfunction, and mortality. Serum lactate trends may predict SMD and can be used as prognosticate markers as well.
Keywords: ventricular dysfunction; lactates; shock; septic; organ failure; echocardiography